Analysis of E-Kinerja Platform Merdeka Mengajar Results in Improving the Work Ethic of Senior High School Teachers in East Kalimantan - Setiono, Ranto; Azainil, Azainil; Gede, Widyamitke (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
Technology-based teacher performance evaluation, such as the e-Kinerja Platform Merdeka Mengajar (PMM), serves as a modern solution for measuring and improving educators' performance. This study aims to describe the e-Kinerja PMM process, the supporting and inhibiting factors in its implementation, and the solutions applied by schools. A qualitative approach is used to analyze the results of e-Kinerja PMM in enhancing teachers' work ethic. The research was conducted at SMA Negeri 1 and SMA Negeri 7 Berau, with data collection techniques including observation, interviews, and documentation. Data analysis follows Miles and Huberman's interactive model, seeking relationships between e-Kinerja PMM and the improvement of teachers' work ethic. The study results show that the e-Kinerja PMM process enhances teachers' work ethic in six aspects: commitment to the profession, discipline and responsibility, creativity and innovation in teaching, enthusiasm and motivation in teaching, professionalism at work, and continuous self-development. Similarly, the supporting and inhibiting factors in implementing e-Kinerja are related to improvements in these six aspects. The solutions implemented by schools in carrying out e-Kinerja also contribute to enhancing teachers' work ethic in these areas. This study affirms that e-Kinerja PMM has the potential to improve teachers' work ethic. Theoretical implications of this research provide academic insights into digital-based performance evaluation. Keywords: e-Kinerja, Platform Merdeka Mengajar, teachers' work ethic, performance evaluation, educational technology